2006
DOI: 10.1021/jp064734v
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Dependent Density Functional Theory Investigation of the Spectroscopic Properties of the β-Subunit in C-Phycocyanin

Abstract: By using time-dependent density functional theory combined with the polarizable continuum model, a satisfactory assignment of the absorption and circular dichroism spectra and energy transfer flow of the beta-subunit in C-phycocyanin (C-PC) was achieved when the protonation of beta-84 and beta-155 phycocyanobilin (PCB) and their interaction with the protein moiety in C-PC have been taken into account. We attribute the main peak for both beta-84 and beta-155 as arising from the pi electron excitation of the pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…To address this possibility, we use electronic structure models (implemented in Gaussian 2009 [64]) to compute electronic transition dipoles at various displacements in the HOOP coordinate for an individual phycocyanobilin pigment. The calculations are carried out in a dielectric environment (dielectric constant equal to 4.0 in the 'polarizable continuum model' [64]) to simulate the surrounding protein environment [65,66]. Because the 'best' choice of an electronic structure method is not clear a priori, we employ two different models to ensure robust insights: (i) B3LYP functional with 6-311G(d) basis set; (ii) Hartree-Fock with 6-311G(d) basis set.…”
Section: Non-condon Character Of the Hoop Vibrational Modementioning
confidence: 99%
“…To address this possibility, we use electronic structure models (implemented in Gaussian 2009 [64]) to compute electronic transition dipoles at various displacements in the HOOP coordinate for an individual phycocyanobilin pigment. The calculations are carried out in a dielectric environment (dielectric constant equal to 4.0 in the 'polarizable continuum model' [64]) to simulate the surrounding protein environment [65,66]. Because the 'best' choice of an electronic structure method is not clear a priori, we employ two different models to ensure robust insights: (i) B3LYP functional with 6-311G(d) basis set; (ii) Hartree-Fock with 6-311G(d) basis set.…”
Section: Non-condon Character Of the Hoop Vibrational Modementioning
confidence: 99%
“…49 We also see TDDFT's use in studying various fullerenes. [50][51][52][53][54][55] TDDFT is also finding many uses in biochemistry [56][57][58][59][60][61][62][63][64][65][66] where, for example, DNA bases are under examination (an overview of this area may be found in Ref. 67).…”
Section: Introductionmentioning
confidence: 99%
“…The initial geometries were obtained from the data set of crystal structures of APC isolated from T. elongatus (PDB ID:1B33, resolution of 3.5 Å), the hydrogen atoms were added using Gaussview 5.0. Albeit the crystal structure is unable to show evidence for protonation, our previous investigations have demonstrated that protonation was important and most likely exists in PCBs. Moreover, the remarkable effects of short‐range interactions on electronic coupling caused by an aspartate residue nearby PCBs have also been found in our previous study .…”
Section: Computational Detailsmentioning
confidence: 86%